Efficacy of Ibrutinib in the Treatment of Monoclonal Gammopathy of Renal Significance with C3 Deposits Secondary to Chronic Lymphocytic Leukemia - Padua, Laura De; Apponi, Francesca; Tomei, Gabriella; Bondatti, Franco; Ferrari, Antonella (Archives of Clinical and Biomedical Research, 2025)
Background: The new International Kidney and Monoclonal Gammopathy Research Group consensus definition of monoclonal gammopathy of renal significance includes all B cell or plasma cell proliferative disorders that produce a nephrotoxic monoclonal immunoglobulin. A novel entity characterized by glomerulonephritis with isolated glomerular C3 deposits has been described. Methods: Here we present the case of a patient with a previous diagnosis of Chronic Lymphocytic Leukemia with associated Monoclonal Gammopathy, who showed onset of proteinuria and was diagnosed with C3 glomerulopathy on renal biopsy. Since early treatment tailored to the to underlying clonal B-cell disorder can improve renal outcome, we started treatment with ibrutinib. Results: Disease assessment after 6 months of therapy showed partial hematological response and renal response with normalization of proteinuria. Conclusions: In our patient with Monoclonal Gammopathy of Renal Significance secondary to Chronic Lymphocytic Leukemia and aggressive renal disease, the ibrutinib based regime proved to be an appropriate strategy to target the lymphocyte clone and to improve renal damage.